DAKWAH ALA QURAISH SHIHAB: (Penafsiran Surat Al-Nahl : 125) - Nugraha Andri Afriza; Nana Gustianda (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2024)
Da'wah is the first command given by Allah to the Prophet Muhammad as an acknowledgment of his apostleship. The same thing was also ordered to humans other than the Prophet Muhammad to invite people to the right path or Islamic teachings. There are many methods of preaching, but the Koran explains how preaching should best be done. Q.S an-Nahl: 125 explains how to preach according to the guidance, to be able to understand what the Koran conveys so that it is more targeted, we can see how Quraish Shihab interprets this verse.Keywords : Dakwah, Quraish Shihab, Tafsir